A Narrative Inquiry Into Pre-Service English Teachers' Temporal Investments in Their Initial Education Curriculum - María Cristina Sarasa (Asociación Colombiana de Profesores de Ingles, 2017)
This paper originates from a narrative inquiry into English teachers' identity carried out with 24 undergraduates at an Argentinean university English as an international language teacher education program. Grounded in a narrative conceptualization of identity, this enquiry gathered participants' storied field texts that were analyzed narratively. This paper explores how students' narratives disclosed the exercise of their agency concerning the program's curriculum by deciding how and when (not) to invest, reinvest, or divest their personal time in scheduled courses. We problematize these categories originating in undergraduates' narratives, connecting them to literature in the field of curriculum. The conclusion suggests the implications these situated findings entail for English as an international language teacher education curriculum and research.